Dating Beowulf Studies in intimacy - Remeiner, Daniel C.; Weaver, Erica (Manchester University Press, 2019)
Featuring essays from some of the most prominent voices in early medieval English studies, Dating Beowulf: studies in intimacy playfully redeploys the word 'dating', which usually heralds some of the most divisive critical impasses in the field, to provocatively phrase a set of new relationships with an Old English poem. This volume presents an argument for the relevance of the early Middle Ages to affect studies and vice versa, while offering a riposte to anti-feminist discourse and opening avenues for future work by specialists in the history of emotions, feminist criticism, literary theory, Old English literature, and medieval studies alike. To this end, the chapters embody a range of critical approaches, from queer theory to animal studies and ecocriticism to Actor-Network theory, all organized into clusters that articulate new modes of intimacy with the poem.